How Much Should Americans Be Saving for Retirement? - Bernheim, B. Douglas; Forni, Lorenzo; Gokhale, Jagadeesh; Kotlikoff, Laurence J (American Economic Review, 2000)
How Much Should Americans Be Saving for Retirement? by B. Douglas Bernheim, Lorenzo Forni, Jagadeesh Gokhale and Laurence J. Koltikoff. Published in volume 90, issue 2, pages 288-292 of American Economic Review, May 2000